Assessing the current state of university-based business incubators in Canada. Issue 3 (June 2023) - Yasin, Naveed; Majid Gilani, Sayed Abdul
This paper explores the current state of university-based business incubators (UBIs) in Canada by utilizing both secondary and primary data obtained through desk-based secondary research and semi-structured interviews with UBI managers, academics, and support staff. These data informed the development of nine cases of UBIs in Canada. The data were collected from VoIP (Voice-Over-Internet-Protocol) based semi-structured interviews with 32 participants during the COVID-19 pandemic (March 2021–February 2022), from which 9 cases were developed during the pandemic. The key themes derived from the findings were the development of communication skills, curriculum development, extra-curricular activities, industry engagement, innovation, research skills and strategic thinking. The originality of this study lies in its identification of the current state of UBI activities as well as its assessment of the broad range of activities and provisions among Canadian UBIs. The empirical development of showcasing these initiatives is also novel for the efficacy of UBIs concerning institutional and managerial decision-making and operational planning. There are implications for academics, senior management in higher education, entrepreneurs, policymakers and other stakeholders in the entrepreneurship ecosystem.